Sistemas agroalimentares locais: diagnóstico da agricultura familiar alfenense - Martins, Maria Luísa Monteiro (2023)
This research explores the social category “family farming” in the municipality of Alfenas-MG. The objective was to understand the socioeconomic reality of Alfenense family farmers and their contribution to food sovereignty in the municipality. The study problematizes the impact caused on the Brazilian territorial dynamics by the globalization of agriculture, empirically, presents socioeconomic aspects, and identifies the perception of farmers on topics relevant to the category and society as a whole. This purpose was achieved through documentary and field research, and descriptive paths. In the first, data from the IBGE Agricultural Census, the EMATER-MG Annual Activity Report, and Public Call 001/2022 of the Alfenas-MG City Hall were used. In the second, a class with objective and discursive questions was applied. The study confirmed the hypothesis that family farming contributes to food sovereignty in the municipality of Alfenas-MG.